2001
DOI: 10.1074/jbc.m101977200
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor Small Heterodimer Partner as a Novel Coregulator of Nuclear Factor-κB in Oxidized Low Density Lipoprotein-treated Macrophage Cell Line RAW 264.7

Abstract: Small heterodimer partner (SHP), specifically expressed in liver and a limited number of other tissues, is an unusual orphan nuclear receptor that lacks the conventional DNA binding domain. In this work, we found that SHP expression is abundant in murine macrophage cell line RAW 264.7 but was suppressed by oxidized low density lipoprotein (oxLDL) and its constituent 13-hydroxyoctadecadienoic acid, a ligand for peroxisome proliferator-activated receptor ␥. Furthermore, SHP acted as a transcription coactivator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 30 publications
2
43
1
Order By: Relevance
“…Short exposure (less than 4 h) of resting macrophages to ox-LDL leads to increased expression of MMP-9 mRNA through activation of NF-κB (Xu et al, 1999). In our experiment, however, U937 monocytic cells were incubated with ox-LDL for more than 24 h. In this case, PPAR-γ-mediated pathway overrides the NF-κB-mediated responses, leading to suppression of MMP-9 mRNA expression (Kim et al, 2001). In primary monocytes, ox-LDL (5-25 µg/ml) in the presence of tumor necrosis factor (TNF)-α and GM-CSF increased slightly MMP-9 activity (Ardans et al, 2002).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Short exposure (less than 4 h) of resting macrophages to ox-LDL leads to increased expression of MMP-9 mRNA through activation of NF-κB (Xu et al, 1999). In our experiment, however, U937 monocytic cells were incubated with ox-LDL for more than 24 h. In this case, PPAR-γ-mediated pathway overrides the NF-κB-mediated responses, leading to suppression of MMP-9 mRNA expression (Kim et al, 2001). In primary monocytes, ox-LDL (5-25 µg/ml) in the presence of tumor necrosis factor (TNF)-α and GM-CSF increased slightly MMP-9 activity (Ardans et al, 2002).…”
Section: Discussionmentioning
confidence: 49%
“…The differences between our data and the previous ones might be explained by considering context or concentration-dependent influence of ox-LDL on macrophage gene expression. Ox-LDL activates NF-κB first, then PPAR-γ (Han et al, 2000;Kim et al, 2001). Short exposure (less than 4 h) of resting macrophages to ox-LDL leads to increased expression of MMP-9 mRNA through activation of NF-κB (Xu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…SHP was found to be a coactivator of NF-κB in macrophages and this activation of NF-κB was secondary to SHP binding to the NF-κB p65 subunit with enhanced binding of the p65/p50 complex to the NF-κB consensus sequence (14). We and others have previously shown that ARR activation of NF-κB is essential in ARR-mediated apoptosis (31,35).…”
Section: Discussionmentioning
confidence: 99%
“…SHP modulation of gene expression is due to its ability to associate with other proteins and it has been found to heterodimerize with a large number of nuclear receptors, including the thyroid hormone receptor, retinoic acid receptor, retinoid X receptor, estrogen receptor, glucocorticoid receptor, and hepatocyte nuclear factor-4 (13). In contrast, SHP has been found to activate the NF-κB and Peroxisome Proliferator-Activated Receptor γ (PPARγ) nuclear receptors (14,15). At least three separate and distinct pathways seem to be used by SHP to silence gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation